Vantaggio o perdita? Le facce della misericordia nel De opere et eleemosynis di Cipriano - MEJZNER, MIROSLAW (Gregorianum, 2017)
De opere et eleemosynis of Cyprian is the first Christian text dedicated entirely to charity. The purpose of the study consists of reading it in a key of psychology, based on the theory of stress, advanced by Stevan E. Hobfoll. The American psychologist noted that situations in which resources are threatened, cause stress. On this basic assumption, he has built a model of behaviour called Conservation of Resources. The argumentation of Cyprian fits perfectly into this model and he himself appears as a leader who knows eliminate anxiety and drive men to a desired behaviour. In the article, an analysis and classification of the arguments applied by Cyprian in favour of charity is also proposed, as well as his modes of expression. In fact, based on many biblical passages, he considered alms a participation in God’s mercy, fully manifested in the saving work of Christ.